Pregnant Checkup Management System For Private Clinic - Shu Wen Pang,; Nurul Aswa Omar, (Applied Information Technology And Computer Science, 2024)
The Pregnant Checkup Management System faces issues such as long queues, inefficiency from duplicating checkup records for staff and patients, wasted time and resources, excessive paper use, and a lack of digitalization. The Pregnant Checkup Management System for Private Clinics in Kluang, Johor is a web-based solution designed to address inefficiencies in the manual recording of pregnant patient checkup information. Developed using the waterfall methodology, the system transitions from paper-based record-keeping to a computerized approach, enhancing security and effectiveness. Acting as an administrator, the head nurse has comprehensive permissions to edit, create, delete, and view information in the system. The findings includes saving time and paper, streamlining the checkup recording process, and providing efficient database storage, eliminating the need for manual searching. Ultimately, the proposed system aims to optimize the management of pregnant checkups in private clinics, offering a smoother and more effective process.